Coastal interdune agroecosystems in the Mediterranean: a case study of the Andalusian navazo. Issue 9 (20th October 2016) - Sánchez, Rubén; Cuellar, Mamem
ABSTRACT: This study focuses on a type of traditional agricultural ecosystem found in southern Spain, called the navazo, which is the product of agricultural activity carried out in coastal interdune systems. We found examples of similar agroecosystems in different Mediterranean regions, such as the masseira in Portugal and the mawasi in the Middle East. The navazo system of farming has been used throughout southwestern Spain for centuries and particularly at the mouth of the Guadalquivir River, the subregion that is the focus of our study. It is an ingenious system in which interconnected cultivated areas are established between dunes. Crops are planted in areas where the water table is close to the surface, meaning water is supplied by capillary action and tidal forces. The energy efficiency of this system and the way it is integrated into the natural environment makes it an interesting example of an inherited agroecosystem and a sustainable agriculture model. Since the continued use of the navazo is threatened by agricultural intensification and urban development pressures, this work aims to characterize this endangered agroecosystem. This study also seeks to preserve related local biocultural knowledge, and to better understand the system's sustainability.